In situ handheld three‐dimensional bioprinting for cartilage regeneration. (25th August 2017) - Di Bella, Claudia; Duchi, Serena; O'Connell, Cathal D.; Blanchard, Romane; Augustine, Cheryl; Yue, Zhilian; Thompson, Fletcher; Richards, Christopher; Beirne, Stephen; Onofrillo, Carmine; Bauquier, Sebastien H.; Ryan, Stewart D.; et al.
Abstract: Articular cartilage injuries experienced at an early age can lead to the development of osteoarthritis later in life. In situ three‐dimensional (3D) printing is an exciting and innovative biofabrication technology that enables the surgeon to deliver tissue‐engineering techniques at the time and location of need. We have created a hand‐held 3D printing device (biopen) that allows the simultaneous coaxial extrusion of bioscaffold and cultured cells directly into the cartilage defect in vivo in a single‐session surgery. This pilot study assessed the ability of the biopen to repair a full‐thickness chondral defect and the early outcomes in cartilage regeneration, and compared these results with other treatments in a large animal model. A standardized critical‐sized full‐thickness chondral defect was created in the weight‐bearing surface of the lateral and medial condyles of both femurs of six sheep. Each defect was treated with one of the following treatments: (i) hand‐held in situ 3D printed bioscaffold using the biopen (HH group), (ii) preconstructed bench‐based printed bioscaffolds (BB group), (iii) microfractures (MF group) or (iv) untreated (control, C group). At 8 weeks after surgery, macroscopic, microscopic and biomechanical tests were performed. Surgical 3D bioprinting was performed in all animals without any intra‐ or postoperative complication. The HH biopen allowed early cartilage regeneration. The results of this study show that real‐time, in vivo bioprinting with cells and scaffold is a feasible means of delivering a regenerative medicine strategy in a large animal model to regenerate articular cartilage.